(untitled) (GAIMS Journal of Medical Sciences, 2026)
The rapid integration of artificial intelligence (AI) into healthcare is transforming clinical practice, medical education, and research. Despite its growing relevance, formal AI literacy remains absent from undergraduate medical curricula in India, creating a gap between technological advancement and medical training. The Competency-Based Medical Education (CBME) curriculum introduced by the National Medical Commission emphasizes digital preparedness and provides an opportunity to address this gap through structured curricular innovation. This editorial proposes the integration of a 20-hour AI literacy module within the MBBS foundation course to equip undergraduate medical students with essential foundational competencies in AI.